2005
DOI: 10.1177/1077559505276686
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Shame Following Sexual Abuse: A Longitudinal Look at Risk and Recovery

Abstract: This study investigated persistence in abuse-related shame during a 6-year period. One-hundred-eighteen sexually abused youth were interviewed at the time of discovery, and again both 1 and 6 years later. Individuals high in shame 1 year following discovery were especially at risk for persistently high levels of shame 6 years later. Youth with high shame for the abuse at 1 and 6 years were the most likely to report clinically significant levels of intrusive recollections at 6 years. Persistent shame may explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
227
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(256 citation statements)
references
References 48 publications
(63 reference statements)
14
227
1
2
Order By: Relevance
“…Other research found that shame moderated adult anger and depressive symptoms after emotional abuse (Harper & Arias, 2004). Although shame had average values in some centrality metrics, the role of shame in the emerging network was below what we expected from previous research (Feiring & Taska, 2005). Shame is an important factor after trauma (Taylor, 2015); however, it is possible that experiences of shame changed over time and with regard to the disclosure and the governmental compensation process in our sample.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Other research found that shame moderated adult anger and depressive symptoms after emotional abuse (Harper & Arias, 2004). Although shame had average values in some centrality metrics, the role of shame in the emerging network was below what we expected from previous research (Feiring & Taska, 2005). Shame is an important factor after trauma (Taylor, 2015); however, it is possible that experiences of shame changed over time and with regard to the disclosure and the governmental compensation process in our sample.…”
Section: Discussioncontrasting
confidence: 93%
“…There is consensus that shame is a common and central reaction to sexual CA and is also strongly connected to the perceived stigma related to it (Feiring & Taska, 2005; Finkelhor & Browne, 1985). Shame was proposed to be a main factor leading to poor adjustment (Feiring, Taska, & Lewis, 1996) and it seems to be a persistent emotion related to the abuse over many years and may also contribute to the maintenance of PTSD symptoms (Feiring & Taska, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In psychological and psychiatric practice, however, self-conscious emotions, which include pride, guilt, embarrassment, humiliation, and shame, are more clinically relevant. The present study focused on shame, because it may interfere the most with healthy psychological functioning (26) and was shown to be predictive of developing depression (27) and PTSD symptoms, including hyperarousal (28). By obstructing effective coping mechanisms, shame often hinders therapeutic progress, to the point that it may even lead to a negative therapeutic outcome (29).…”
Section: Significancementioning
confidence: 99%
“…Le sentiment de culpabilité réfère plutôt à une évaluation émotionnelle négative de ses comportements et de ses actions, et non de sa personne (Lewis, 1971). La honte peut être observée chez les victimes d'AS lorsqu'elles tentent de se cacher en parlant de leur expérience traumatique (Feiring et Taska, 2005). Les enfants peuvent se sentir honteux d'avoir été impliqués dans des comportements sexuels jugés inappropriés (Feiring, Taska et Chen, 2002), alors que la culpabilité est associée au regret d'avoir fait (ou de ne pas avoir fait) certains gestes.…”
Section: Sentiment De Culpabilitéunclassified